THE RELATIONSHIP BETWEEN PRIMARY AND SECONDARY DIMENSIONS OF DIVERSITY WITH HUMAN BEHAVIOR AND BELIEFS: A STUDY ON BLOOD TYPES AND RELIGION IN INDONESIA - grace lovita; meganitri putri; natasha eka novianti; wilbert melvern; ida bagus putu aditya (LIAISON JOURNAL OF BEST, 2022)
This Paper Aims To Determine Whether Or Not There Is A Relationship Between A Person’s Beliefs Regarding Factors In Hofstede’s Cultural Dimensions, Specifically Power Distance And Individualism Vs Collectivism, Their Cross-Cultural Understanding To Their Blood Type And Religious Beliefs. Additionally, This Paper Aims To Determine Whether A Primary Dimension Of Diversity, Blood Type, Or A Secondary Dimension Of Diversity, Religion, Is A Better Indicator Of An Individual’s Behaviour, If At All. A Survey Was Conducted Through Simple Random Sampling Method To Gather Data From As Many Individuals As Possible To Ensure The Validity Of The Research’s Findings. In Total, 30 Questions Were Asked In The Survey Of Which 12 Were About The Individual’s Profile And 18 Were About Their Cross-Cultural Understanding And Their Beliefs On Individualism, Collectivism, And Power Distance.Keywords: Blood Type, Religion, Cross-Cultural Understanding, Hofstede’s Cultural Dimension